Patterning dye-sensitized solar cell photoanodes through a polymeric approach: A perspective. (January 2018) - Bella, Federico; Verna, Alessio; Gerbaldi, Claudio
Abstract: Performances in terms of efficiency and stability of dye-sensitized solar cells (DSSCs) depend on several factors related to the preparation of the device components (electrodes and electrolyte). In particular, patterning techniques recently intruded in the third generation photovoltaic scenario with promising results. In this perspective, we introduce the most interesting strategies proposed for the patterning of photoanodes and cathodes. Afterwards, we propose a novel approach exclusively based on the use of polymeric materials. The resulting DSSC shows a power conversion efficiency equal to 5.33% measured under 1 sun irradiation, and retains the 96% of this value in a prolonged aging test (2000 h at 50 °C).